Willingness to pay for policies to reduce future deaths from climate change: evidence from a British survey. (September 2019) - Graham, H.; de Bell, S.; Hanley, N.; Jarvis, S.; White, P.C.L.
Abstract: Objectives: Without urgent action, climate change will put the health of future populations at risk. Policies to reduce these risks require support from today's populations; however, there are few studies assessing public support for such policies. Willingness to pay (WtP), a measure of the maximum a person is prepared to pay for a defined benefit, is widely used to assess public support for policies. We used WtP to investigate whether there is public support to reduce future health risks from climate change and if individual and contextual factors affect WtP, including perceptions of the seriousness of the impacts of climate change. Study design: A cross-sectional British survey. Methods: Questions about people's WtP for policies to reduce future climate change-related deaths and their perceptions of the seriousness of climate change impacts were included in a British survey of adults aged 16 years and over ( n =1859). We used contingent valuation, a survey-based method for eliciting WtP for outcomes like health which do not have a direct market value. Results: The majority (61%) were willing to pay to reduce future increases in climate change-related deaths in Britain. Those regarding climate change impacts as not at all serious were less willing to pay than those regarding the impacts as extremely serious (OR 0.04, 95% CI 0.02-0.09). Income was also related to WtP; the highest-income group were twice as likely to be willing to pay as the lowest-income group (OR 2.14, 95% CI 1.40-3.29). Conclusions: There was public support for policies to address future health impacts of climate change; the level of support varied with people's perceptions of the seriousness of these impacts and their financial circumstances. Our study adds to evidence that health, including the health of future populations, is an outcome that people value and suggests that framing climate change around such values may help to accelerate action. Graphical abstract: Image 1 Highlights: Little is known about public support for policies to reduce the future health risks of climate change. This study suggests that British adults were willing to pay for such policies. The perceived seriousness of climate change impacts was related to willingness to pay. Those in higher income bands were more willing to pay than those with lower incomes. Future research should investigate willingness to pay using other study designs.